2020
DOI: 10.1186/s43066-020-0022-7
|View full text |Cite
|
Sign up to set email alerts
|

Ascitic calprotectin as a useful marker in the diagnosis of spontaneous bacterial peritonitis in adults

Abstract: Background: Ascitic fluid polymorphonuclear leucocyte count (PMN) is known to be the gold standard for spontaneous bacterial peritonitis (SBP) diagnosis. The aim of this work was to assess ascitic calprotectin for SBP diagnosis. Serum C-reactive protein (CRP), high sensitivity C-reactive protein (hsCRP), nitrous oxide, ascitic PMN, ascitic leucocyte esterase and ascitic calprotectin were measured. Results: The average age of our patients was 55.25 ± 7.89 years, mostly males (n = 51, 63.8%), anti-HCV antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
6
0
0
Order By: Relevance
“…As regard bilirubin level of studied patients, we noted that median total and direct bilirubin were significantly higher in group І (3.2 mg/dl and 1.6 mg/dl, respectively) compared to group II (1.8 mg/dl and 0.65 mg/dl, respectively). Also, these results were similar to data recorded by Abdel-Rahman et al (17) who found that patients with SBP had statistically significant higher median total bilirubin compared to control group (4.2 vs. 2.3 mg/dL) respectively.…”
Section: Discussionsupporting
confidence: 91%
“…As regard bilirubin level of studied patients, we noted that median total and direct bilirubin were significantly higher in group І (3.2 mg/dl and 1.6 mg/dl, respectively) compared to group II (1.8 mg/dl and 0.65 mg/dl, respectively). Also, these results were similar to data recorded by Abdel-Rahman et al (17) who found that patients with SBP had statistically significant higher median total bilirubin compared to control group (4.2 vs. 2.3 mg/dL) respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In line with our findings, Rasmy et al (15) highlighted that (HB, AST, Albumin, TP, bilirubin, creatinine, and urea) were insignificantly different between both studied groups. Parallel to our results, Abdel Rahman et al (18) noted that no substantial variation was existed among SBP group and the group without SBP regarding ( HB, AST, Albumin, TP, bilirubin, and creatinine).…”
Section: Discussionsupporting
confidence: 89%
“…However, there was no statistically significant difference in serum albumin or alanine aminotransferase readings across the groups, although there was a statistically significant difference in aspartate aminotransferase (AST). Furthermore, our findings are consistent with those of Abdel Rahman et al [21], who found that when 80 patients with liver cirrhosis were separated into two equal groups, with and without SBP, the mean values of AST and ALT did not differ substantially between the two groups.…”
Section: Popoiag Et Al [16]supporting
confidence: 92%
“…Patients in the SBP group had significantly greater blood creatinine and urea than patients in the non-SBP group in terms of kidney function tests. Our findings are consistent with those of Metwally et al [15] and Popoiag et al [16], who found that patients in the SBP group had significantly higher serum creatinine than those in the nonSBP group, but not with those of Abdel Rahman et al [21], who found creatinine values to be similar in both groups.…”
Section: Popoiag Et Al [16]supporting
confidence: 92%